Health Impacts of Indiscriminate Dumping of Solid Waste Disposal in Wukari Local Government Area, Taraba State, Nigeria - Ujulu, Peter; Amos, Donald; Maiguwa, Auwalu Ali (Darul Yasin Al Sys, 2025)
This study investigates the health impacts of indiscriminate solid waste disposal in Wukari Local Government Area, Taraba State, Nigeria. The objectives were to identify the composition of waste materials, assess waste management practices among residents, and evaluate the health implications of indiscriminate dumping in the area. Primary data were collected through structured questionnaires distributed randomly across residential areas, markets, schools, workshops, and business centers. A total of 400 household heads were sampled for the study. Data collection included field observations and questionnaire responses, which were analyzed using SPSS Version 25.0 to generate frequency distributions, percentage ratios, and mean values, with findings presented in tabular format for clarity. Results showed that the predominant types of waste generated were polythene (33.4%), followed by cloth/carton/paper (27.3%), crop residue/food remains (18.0%), plastic (15.9%), and cans/tins/bottles (5.4%). The study also revealed that 43.1% of households disposed of waste in open spaces, indicating poor waste management practices. Additionally, the findings suggest that higher educational attainment among residents positively influenced proper waste disposal behavior. The study concludes that indiscriminate dumping poses serious environmental and health risks, and recommends increased public awareness, improved waste management infrastructure, and the enforcement of environmental sanitation policies to mitigate the adverse effects of improper waste disposal.